2020
DOI: 10.1037/xlm0000752
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the formation and consolidation of incidentally learned trust.

Abstract: People make inferences about the trustworthiness of others based on their observed gaze behavior. Faces that consistently look toward a target location are rated as more trustworthy than those that look away from the target. Representations of trust are important for future interactions; yet little is known about how they are consolidated in long-term memory. Sleep facilitates memory consolidation for incidentally learned information and may therefore support the retention of trust representations. We investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Interestingly, while emotion seems to modulate trust learning, and to influence trust judgments (Oosterhof and Todorov, 2008), its direct effect on gaze-cueing is unclear (Dalmaso et al, 2020). On the other hand, the trust learning effect has been replicated under a variety of conditions (Strachan et al, 2016(Strachan et al, , 2020. Notably, across studies trust learning was more consistently observed in the form of decreased trust for invalidcueing faces than as increased trust for valid cues , suggesting greater monitoring of deceptive characters over the cooperative ones.…”
Section: Gaze-cueing Effects On Trustworthiness Judgmentsmentioning
confidence: 98%
“…Interestingly, while emotion seems to modulate trust learning, and to influence trust judgments (Oosterhof and Todorov, 2008), its direct effect on gaze-cueing is unclear (Dalmaso et al, 2020). On the other hand, the trust learning effect has been replicated under a variety of conditions (Strachan et al, 2016(Strachan et al, , 2020. Notably, across studies trust learning was more consistently observed in the form of decreased trust for invalidcueing faces than as increased trust for valid cues , suggesting greater monitoring of deceptive characters over the cooperative ones.…”
Section: Gaze-cueing Effects On Trustworthiness Judgmentsmentioning
confidence: 98%
“…While this is a possible factor contributing to our results, there are reasons to believe that rapid decay of incidental impressions from subtle cues is not the primary driver. First, recent studies (Strachan et al, 2020; have examined the durability of incidental impressions formed during a gazecueing task, and found that the effects were relatively robust to interference and survived for up to a week, though the strength of the effect does fade somewhat over time. Second, the time-frame of our entire study, including both initial and changed behaviour, is similar to the time-frame of previous studies that have used gaze-cues to drive impression formation, albeit without a change in behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…For Experiments 4 and 5, the timeframe between testing sessions is worth consideration, because a recent paper demonstrated that the effects of trust learning can persist for longer than one might expect; up to a week (Strachan et al, 2020). In their study, Strachan and colleagues (2020) asked participants to rate how trustworthy wholly valid and invalid faces were on four occasions; before a gaze-cueing task, immediately afterwards, after 90 minutes and after a one-week interval.…”
Section: Limitationsmentioning
confidence: 99%
“…The MATG, first published by Collins 1 in his master’s thesis, is a game of strategic interaction combining features of two commonly used games, the multi-arm bandit game ( Robbins, 1952 ) and the trust game ( Berg et al, 1995 ). The trust game was first used by Berg et al (1995) to examine behavior in one-shot interactions and later used by other researchers to study behavior in repeated interactions ( Dubois et al, 2012 ), group interactions ( Ignat et al, 2019 – control condition), and over various periods of time ( Strachan et al, 2020 ). The multi-arm bandit game ( Robbins, 1952 ) has been used in various psychological studies to explore exploration-exploitation behavior in both animals and humans (e.g., Cohen et al, 2007 ).…”
Section: Empirical Study Methodsmentioning
confidence: 99%